Optimizing management to enhance multifunctionality in a boreal forest landscape. Issue 1 (14th October 2016) - Triviño, María; Pohjanmies, Tähti; Mazziotta, Adriano; Juutinen, Artti; Podkopaev, Dmitry; Le Tortorec, Eric; Mönkkönen, Mikko
Summary: The boreal biome, representing approximately one‐third of remaining global forests, provides a number of crucial ecosystem services. A particular challenge in forest ecosystems is to reconcile demand for an increased timber production with provisioning of other ecosystem services and biodiversity. However, there is still little knowledge about how forest management could help solve this challenge. Hence, studies that investigate how to manage forests to reduce trade‐offs between ecosystem services and biodiversity are urgently needed to help forest owners and policy makers take informed decisions. We applied seven alternative forest management regimes using a forest growth simulator in a large boreal forest production landscape. First, we estimated the potential of the landscape to provide harvest revenues, store carbon and maintain biodiversity across a 50‐year time period. Then, we applied multiobjective optimization to identify the trade‐offs between these three objectives and to identify the optimal combination of forest management regimes to achieve these objectives. It was not possible to achieve high levels of either carbon storage or biodiversity if the objective of forest management was to maximize timber harvest revenues. Moreover, conflicts between biodiversity and carbon storage became stronger when simultaneously targeting high levels of timber revenues. However, with small reductions in timber revenues, it was possible to greatly increase the multifunctionality of the landscape, especially the biodiversity indicators. Forest management actions, alternative to business‐as‐usual management, such as reducing thinnings, extending the rotation period and increasing the amount of area set aside from forestry may be necessary to safeguard biodiversity and non‐timber ecosystem services in Fennoscandia. Synthesis and applications . Our results show that no forest management regime alone is able to maximize timber revenues, carbon storage and biodiversity individually or simultaneously and that a combination of different regimes is needed to resolve the conflicts among these objectives. We conclude that it is possible to reduce the trade‐offs between different objectives by applying diversified forest management planning at the boreal landscape level and that we need to give up the all‐encompassing objective of very intensive timber production, which is prevailing particularly in Fennoscandian countries.